Business Ownership and Economic Growth in 23 OECD Countries - Martin Carree; André van Stel; Roy Thurik; Sander Wennekers (Tinbergen Institute, 2000)
In the present paper we address the relationship between the extentof business ownership (self-employment) and economic development. We will focusupon three issues. First, how is the equilibrium rate of business ownershiprelated to the stage of economic development? Second, what is the speed ofconvergence towards the equilibrium rate when the rate of business ownership is out-of-equilibrium? Third, to what extent does deviating from the equilibrium rate of business ownership lead to less economic growth? Hypotheses concerning all three issues are formulated setting up a new two-equation model. We findconfirmation for the hypothesised effects using a data panel of 23 OECD countries. An important policy implication of our exercises is that low barriers to entry and exit of self-employed/businesses are necessary conditions for the equilibrium seeking mechanisms that are vital for a sound economic development.
Keywords: L16; O12; 330; business ownership; economic growth; entrepreneurship; Eigentümerstruktur; Wirtschaftswachstum; OECD-Staaten